A survey of overall life satisfaction and its association with breast diseases in Chinese women. (7th December 2015) - Bai, Aili; Li, Haixin; Huang, Yubei; Liu, Xueou; Gao, Ying; Wang, Peishan; Dai, Hongji; Song, Fengju; Hao, Xishan; Chen, Kexin
Abstract: To investigate the association between overall life satisfaction and healthy lifestyle, knowledge of breast cancer, physical examination, and detection rate of breast cancer and benign breast disease in Chinese women. In a multicentered breast disease screening program in China, we enrolled 33, 057 women aged 45–65 years without prior diagnosis of breast cancer. After completing an epidemiological questionnaire, all participants were examined by clinical breast examination, breast ultrasound, and mammography independently. All breast cancer cases and a selected sample of benign breast diseases were confirmed pathologically. Univariate and multivariate odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to estimate the association between life satisfaction and lifestyle, knowledge of breast cancer, physical examination, and detection rate of breast diseases. Overall life satisfaction was positively associated with women's healthy lifestyle. Compared with less satisfied women, satisfied women were less likely to be smokers (OR = 0.54; 95% CI: 0.47–0.62), have more exercise (OR = 1.49; 95% CI: 1.26–1.75), eat less fried (OR = 0.60; 95% CI: 0.50–0.71), smoked (OR = 0.54, 95% CI: 0.47–0.63), pickled (OR = 0.66, 95% CI: 0.55–0.79), and grilled (OR = 0.63, 95% CI: 0.54–0.74) foods. Satisfied women were more likely to have knowledge of breast cancer (OR = 1.48, 95% CI: 1.29–1.70), and have regular physical examinations (OR = 1.11, 95% CI: 1.01–1.12). Compared to less satisfied women, we found significantly lower detection rate of benign breast diseases (OR = 0.90, 95% CI: 0.82–0.99), and lower but nonsignificant detection rate of breast cancer (OR = 0.66, 95% CI: 0.35–1.25) in satisfied women. Women with a higher overall life satisfaction are more likely to have healthy lifestyle, knowledge of breast cancer, and regular physical examination, thus resulting in a lower detection rate of breast diseases in screening. Abstract : In this study, we found women with higher overall life satisfaction were associated with significantly lower detection rate of benign breast diseases, and a lower, though nonsignificant detection rate of breast cancer. The inverse association may be explained, at least in part, by the positive association between overall life satisfaction and healthy lifestyle, knowledge of breast cancer, and regular physical examination.